Effects of boric acid pretreatment on the properties of four selected malaysian bamboo strips - Mohd Yusof, Norwahyuni; Hua, Lee Seng; Md Tahir, Paridah; James, Redzuan Mohammad Suffian; Al-Edrus, Syeed Saifulazry Osman; Dahali, Rasdianah; Muhammad Roseley, Adlin Sabrina; Fatriasari, Widya; Kristak, Lubos; Lubis, Muhammad Adly Rahandi; Reh, Roman (MDPI, 2023)
Bamboo requires treatment to extend its service life. However, as bamboo strips could serve as a suitable candidate for lamination, the treatment may affect its bendability. The current study investigated the effects of boric acid treatment on the physical, mechanical, adhesion, and morphological properties of bamboo strips. Owing to their availability and popularity in local industries, four Malaysian bamboo species were used in this study, namely Gigantochloa scortechinii, Gigantochloa levis, Dendrocalamus asper, and Bambusa vulgaris. These four species’ bamboo strips were treated with 5% boric acid and their properties were evaluated. The findings revealed that the boric acid treatment had varying degrees of effect on the properties of the bamboo. Despite having lower treatability and stability, both G. scortechinii and G. levis have greatly superior mechanical properties that justify their use in the production of laminated products. The boric acid treatment was found to provide several benefits to bamboo strips intended for lamination, including increased wettability, dimensional stability, and mechanical strength.